Keputusan Petani Mengadopsi Usahatani Padi Organik di Desa Pringkasap - Cahyaningsih, Cahyaningsih; Suprehatin, Suprehatin (Journal of Agribusiness and Community Empowerment (JACE), 2021)
Organic farming is not the only potential solutions to overcome the problems of conventional farming systems by offering positive impacts on health and environment but also to fulfill the growing demand for healthier food. However, the growing demand for organic food was not responded simultaneously by an increase in the supply of organic food. This means that there is opportunity to increase participation of farmers to adopt organic rice farming systems. This study aims to analyze the adoption rate and factors affecting farmer adoption of organic rice farming system. This study used primary data of 32 organic and conventional farmers in Pringkasap Village Subang Regency. The respondents were chosen using census method for organic farmers and purposive sampling for conventional farmers.The data was analyzed used descriptive statistics and logistic regression. The results showed that the number of farmers adopted organic rice only 6.25 percents amongst the 265 rice farmers in Pringkasap Village. The results also showed that education, farmed land, farmer’s perception of the relative advantage of organic farming and number of family members are factors that significantly affect the adoption of organic rice farming in Pringkasap Village.